Dental caries and treatment needs among 12 year-old school children in Heet city/Al-Anbar governorate/Iraq - Neamat M Al-Ani; Sulafa K El-Samarrai (College of Dentistry/ University of Baghdad, 2014)
Background: Dental caries is one of the most prevalent chronic diseases of people worldwide that lead to the pain and disability across all age groups and still consider as a major cause of tooth loss. The aim of this study was to assess the prevalence and severity of dental caries and treatment needs among school children in Heet city. Materiales and methods: The sample included all school children at age of (12 years old) males and females from urban areas in Heet city. Diagnosis and recording of dental caries and treatment needs were done according to the criteria of WHO. Results: The prevalence of dental caries was (90.2%). The DMFS/dmfs values were (5.85±0.168, 1.57±0.146) respectively for the total sample. Females were found to have higher value as compared to males with statistically highly significant difference (P< 0.01) for DMFS, while the opposite picture was found for dmfs. The higher percentage of examined children were in need of preventive or fissure sealant (91.6%), followed by those in need of one surface filling (80.4%). Conclusions: School children were found to have a high prevalence of dental caries, thus there is a need for preventive programs among those children.